By your leave – the English High Court gives guidance on when directors subject to competition disqualification orders may obtain limited permission to act. Issue 1 (April 2020) - Das, Deba; Wylde, Daniel; Tang, Sophie
Abstract : In Stamatis and Davies v. Competition and Markets Authority, Re Fourfront Group Ltd, the English High Court has for the first time considered aspects of the CMA's directors disqualification regime. The CMA regards the power to disqualify directors for competition law infringements as an important tool in its enforcement of competition law. The judgment in Stamatis and Davies v. CMA provides useful guidance on the approach of the English courts to applications by an individual subject to a competition disqualification undertaking for permission to act as a director, under section 17 of the Company Directors Disqualification Act 1986. This article looks at the way the court approached the principles that apply to applications in the non-competition context and highlighted some important considerations that are specific to the competition regime. This article also considers how the judgment may influence the manner in which the CMA approaches its use of its director disqualification powers in the future.